Editorial Acknowledgements and Introduction to the Special Issue on EDM Journal Track (Journal of Educational Data Mining, 2018)
The 11th EDM Conference was held in Buffalo from July 15 to July 18, and for the fourth time it held a Journal track which this year was edited by Min Chi and Irena Koprinska. The Journal track allows papers submitted to JEDM to be presented at the conference. A summary is available in the proceedings, and the full text is published in the Journal.